Perancangan Sistem Pencatatan Stok Barang Berbasis Web Menggunakan Metode Waterfall (Studi Kasus : Toko Bangunan Karya Putra 2) - Syah Rizal, Muhammad; Apriyanto, Budi (CV. Shofanah Media Berkah, 2024)
In the digital era, stock management of goods such as the retail industry of building stores is one of the most important aspects. Toko Bangunan Karya Putra II is one of them that still manages stock management using conventional methods in the process of recording stock of goods. Karya Putra II Building Store, located in the South Tangerang City area, provides building goods such as bricks, cement, sand, and other building tools. Stock recording, inventory management, and supplier data management are still carried out in the conventional way, namely using paper so as to allow for data writing errors, inaccurate incoming goods data, to be less efficient for employee labor. This research aims to build a system that can replace conventional methods with web-based information systems that are expected to facilitate the management of building stores. This system uses the waterfall method and is created using the JavaScript programming language and using a PostgreSQL database. Based on the test results obtained using two system methods, Black Box testing and White Box testing is a system that is built both functionally and the structure of the program code can be run properly according to the expected function. Broadly speaking, the system created has fulfilled the main function in data processing for stock recording systems, such as adding data, displaying data, changing data and deleting data.